The Classical Guidance Service Program To Develop Student Engagement - Ria Riyani Kusnadi; Syari Fitrah Rayaginansih; Ananda Rachmaniar (Ma'soem University, 2025)
Abstract: Student engagement constitutes a critical aspect of the learning process, encompassing behavioural, emotional, and cognitive dimensions. These three components collectively determine the extent of students' active participation in educational activities and significantly influence their academic achievement. When student engagement is low, students are less likely to reach optimal learning outcomes. This study aims to investigate the effectiveness of classical guidance services in enhancing student engagement among 11th-grade students at SMA Al Ma’soem during the 2024/2025 academic year. This research employs a quantitative approach using a pre-experimental one-group pre-test post-test design. The sample consists of 31 students, selected through simple random sampling. The results revealed that classical guidance services did not produce a statistically significant improvement in student engagement, as indicated by a p-value of 0.747 and a t-value of -0.325. Thus, no significant difference was observed between the pre-test and post-test scores, leading to the acceptance of the null hypothesis (H0) and the rejection of the alternative hypothesis (H1). These findings suggest that the classical guidance program, in its current form, is not practical in fostering higher levels of student engagement. Therefore, alternative intervention strategies should be considered, such as incorporating more interactive and experiential learning methods, to better support and enhance student engagement in the learning process.